Laser Induced Temperature Perturbation on Ultramicroelectrodes: Unsupported Solutions in Nonaqueous Methanol. Issue 1 (19th January 2022) - Gutierrez-Portocarrero, Salvador; Subedi, Pradeep; Alpuche Aviles, Mario A.
Abstract : Temperature dependence studies of electrochemical parameters provide insight into electron transfer processes. In cases where adding excess electrolyte causes experimental complications, e.g., colloidal systems, organic or biological samples, it is preferable to deal with the high resistivity of the medium. We validate the use of unsupported and weakly-supported solutions in thermoelectrochemical experiments. The temperature dependence of the diffusion coefficient allows calibration of the steady-state current to measure changes when a continuous-wave (CW) ultraviolet laser, λ = 325 nm, illuminates an ultramicroelectrode (UME) from the front. Calibrating the steady-state current ratios, before and after heating with a thermostatic bath, allows temperature measurements within an accuracy of 0.6 K. The solutions are without supporting electrolytes in methanol, a volatile solvent, and we use a model that accurately describes the viscosity and temperature dependence of the solvent. We calculated the temperature and derived an equation to estimate the error in the temperature measurement. A numeric method yields satisfactory results, considering the changes for both diffusion coefficients and viscosity explicitly, and predicts the thermostatic temperature bath, agreeing with the theoretical model's error. In unsupported solutions, the ferrocene diffusion coefficient and the iodide apparent diffusion coefficient follow the expected increase with temperature. Under CW laser illumination, the UME temperature increase is: ΔT = 4 ± 1 K.